Effect of Electron-Beam Irradiation on the Growth Profile and Fatty Acid Composition of Botryococcus sp. - Windra Yuniarsih; Heli Siti Halimatul; Asri Peni Wulandari (Biosaintifika: Journal of Biology & Biology Education, 2018)
Botryococcus sp. is an economically important microalgae as it contains carbohydrates, lipids, proteins, and a number of phytochemicals. The high concentrations of saturated fatty acids (SFAs) and monounsaturated fatty acids (MUFAs) in this strain also a valuable source for production of biofuel. Mutagenic engineering using irradiation has been known to increase the content of these biomass. The aim of this study is to know the effect of electron-beam irradiation to the growth profile and fatty acid composition of Botryococcus sp. In this study, Botryococcus sp. adjusted an optical density 1.0 after being exposed to different doses of electron-beam irradiation (160 kGy, 240 kGy, and 320 kGy) and induced random mutagenesis for strain improvement was observed based on high energy (1.5 MeV and 2 mA). Several mutants obtained were designated as strain B160, B240, and B320, respectively. The profile growth was significantly different between control (0 kGy) and irradiated microalgae strain. The highest growth is found in B320 mutant. Fatty acid of Botryococcus sp. control produced 7 fatty acids, B160 produced 7 fatty acids, B240 produced 6 fatty acids, whereas B320 produced 9 fatty acids. B320 produced hydrocarbon and phtalic acid as well as fatty acids. Total SFAs and MUFAs of B240 was increased 1.6 times compared to the wild type. The results would give some implications to improve the quality of biodiesel from Botryococcus sp.